The Effect Of Oral Anticoagulation Agents On Hemoglobin Levels in Reproductive Age Women [7D]. (May 2018) - Gonzalez, Aaron Herrera; Stough, Alexandra; Palacio, Danica; Palvia, Vijay; Anasti, James
Abstract : INTRODUCTION: Oral anticoagulation in reproductive age women is not uncommon. Some studies have reported increased incidence of abnormal uterine bleeding and heavy menstrual bleeding in those receiving anticoagulation. However, studies comparing the effect of different oral anticoagulants on hemoglobin levels on menstruating women are lacking. METHODS: We retrospectively reviewed charts of reproductive age women on oral direct activated Factor X inhibitors (FXaI), vitamin K antagonist (vKa), or aspirin (ASA). Demographics and indication for anticoagulation were recorded. Hemoglobin before and 6 to 12 months after initiation of oral anticoagulation were recorded. Pre and post treatment hemoglobin values were compared using paired t-test for each individual anticoagulant and ANOVA was employed to compare initial Hemoglobin levels and pre and post treatment Hemoglobin differences. RESULTS: FXaI, vKa, ASA groups included 91, 73 and 68 patients, respectively. They did not differ in mean age (44.2 ± 6.2 yrs) or BMI (32.5 ± 8.1 kg/m 2 ). Indications for FXaI were Deep Vein Thrombosis (DVT) or Pulmonary Embolism (PE) (64/91), Atrial fibrillation (Afib) (8/91) or antiphospholipid syndrome(7/91). vKa was used for DVT/PE (28/73), stroke (12/73), or Afib (10/73). ASA indications included stroke (27/68), DVT/PE (11/68), or Factor V Leiden (10/68). Post treatment Hemoglobin values were less than 2% lower than pretreatment Hemoglobin levels in all groups. This was not clinically or statistically significant. Differences in Hemoglobin were similar between groups. CONCLUSION: There was no clinically significant decrease in Hemoglobin levels in menstruating women receiving oral anticoagulants at 6 to 12 months post initiation of oral anticoagulation.